(Understanding Religious Embodiment Patterns of Children in Social Activities)) - Adynata, Fuji kusuma (JUPE : Jurnal Pendidikan Mandala, 2024)
The abstract contains a brief description of the research problem and objectives, methods used, and research results.   The pressure for writing abstracts is mainly on research results.   Abstracts are written in Indonesian and English.  Abstract typing is done single-spaced with narrower margins than the right and left margins of the main text. Key words need to be included to describe the problem domain being researched and the main terms that underlie the implementation of the research.  Key words can be single words or combinations of words. Number of key words 3-5 words.  These keywords are necessary for computerization.  Searching for research titles and abstracts is made easier with these keywords